Odd one out - Park, Louise; May, Kyla (North Mankato, Minnesota Picture Window Books, a Capstone imprint, 2015)
Addie, officially known as Star Girl, is having some trouble fitting in at the Space Education and Action School, but she hopes her second mission will be a success--she and Grace (Comet XS), who does not trust her, must seek out the source of the pollution that is poisoning the intelligent vine aliens on the planet Plantagan
A gift from book Africa
Scientific Fictions
1 2 13 15
NEW_ZTN_GN
Keywords: Air -- Pollution -- Juvenile fiction; Life on other planets -- Juvenile fiction